Jual Beli Hak Milik Atas Tanah Yang Belum Bersertifikat - I Made Handika Putra; I Ketut Sukadana; Luh Putu Suryani (Jurnal Analogi Hukum, 2019)
The most powerful property rights are property rights over land, the way to obtain ownership rights is the transfer of rights, one of which is by buying and selling, in buying and selling activities with land objects that are very vulnerable to land problems, one of which is buying and selling land without a certificate. From that the author is interested in conducting research in the form of a thesis with the title of Sale and Purchase of Property on Land that is not yet certified. By using the formulation of the problem: 1) What the Procedure for transitioning rights to land that has not been certified; 2) What are the legal consequences of buy and sell land that has’nt had been certified. The research method used is a normative research method. Transferable property means to move from someone to another party due to legal actions, one of which is by buying and selling, the number of problems in the transfer of rights due to the sale and purchase of land for which there is no certificate, due to legal sale and purchase the transfer of land rights and the absence of legal certainty of holders of land rights.